Influence of inhaled nitric oxide on gas exchange during normoxic and hypoxic exercise in highly trained cyclists - Sheel, A. W.; Edwards, M. R.; Hunte, G. S.; McKenzie, D. C. (Journal of Applied Physiology, 2001)
This study tested the effects of inhaled nitric oxide [NO; 20 parts per million (ppm)] during normoxic and hypoxic (fraction of inspired O2 = 14%) exercise on gas exchange in athletes with exercise-induced hypoxemia. Trained male cyclists (n = 7) performed two cycle tests to exhaustion to determine maximal O2 consumption (O2 max) and arterial oxyhemoglobin saturation (SaO2, Ohmeda Biox ear oximeter) under normoxic (O2 max = 4.88 ± 0.43 l/min and SaO2 = 90.2 ± 0.9, means ± SD) and hypoxic (O2 max = 4.24 ± 0.49 l/min and SaO2 = 75.5 ± 4.5) conditions. On a third occasion, subjects performed four 5-min cycle tests, each separated by 1 h at their respective O2 max, under randomly assigned conditions: normoxia (N), normoxia + NO (N/NO), hypoxia (H), and hypoxia + NO (H/NO). Gas exchange, heart rate, and metabolic parameters were determined during each condition. Arterial blood was drawn at rest and at each minute of the 5-min test. Arterial PO2 (PaO2), arterial PCO2, and SaO2 were determined, and the alveolar-arterial difference for PO2 (A-aDO2) was calculated. Measurements of PaO2 and SaO2 were significantly lower and A-aDO2 was widened during exercise compared with rest for all conditions (P < 0.05). No significant differences were detected between N and N/NO or between H and H/NO for PaO2, SaO2 and A-aDO2 (P > 0.05). We conclude that inhalation of 20 ppm NO during normoxic and hypoxic exercise has no effect on gas exchange in highly trained cyclists.